2014
DOI: 10.1016/j.jtcvs.2013.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Combined heart-kidney transplant improves post-transplant survival compared with isolated heart transplant in recipients with reduced glomerular filtration rate: Analysis of 593 combined heart-kidney transplants from the United Network Organ Sharing Database

Abstract: Performance of combined HKTx is increasing out of proportion to isolated HTx. eGFR is an important determinant of improved HTx survival. Combined HKTx recovers post-transplant survival in patients with eGFR <37 mL/minute and can be recommended in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
111
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 19 publications
4
111
0
11
Order By: Relevance
“…По мнению T. Karamlou с соавт. [6], это обусловле но непредсказуемостью изменения функции почки после ТС. В описанном случае умеренная дисфун кция сердечного трансплантата в раннем послеопе рационном периоде второй трансплантации сердца могла стать одной из причин утраты функции перво го почечного трансплантата.…”
Section: клинический примерunclassified
See 1 more Smart Citation
“…По мнению T. Karamlou с соавт. [6], это обусловле но непредсказуемостью изменения функции почки после ТС. В описанном случае умеренная дисфун кция сердечного трансплантата в раннем послеопе рационном периоде второй трансплантации сердца могла стать одной из причин утраты функции перво го почечного трансплантата.…”
Section: клинический примерunclassified
“…Потребность в ПТСП постоянно растет, что под тверждается и общемировым опытом [6,9]. В на шем Центре на сегодняшний день наблюдаются 6 реципиентов сердечного трансплантата, находя щихся на диализной терапии и включенных в лист ожидания трансплантации почки.…”
Section: клинический примерunclassified
“…Lower eGFR is a risk factor for death after heart transplant (59). Five years after a heart transplant alone, 11% of recipients will require RRT or have an eGFR,30 ml/min per 1.73 m 2 (60).…”
Section: What Is the Evidence To Support Left Ventricular Devices Fromentioning
confidence: 99%
“…The authors concluded that SHK should be considered in heart transplant candidates with kidney failure requiring dialysis, but that for kidney disease not requiring dialysis, further study is needed (61). Another study from the United Network for Organ Sharing identified 26,183 heart transplant recipients and 593 SHK recipients and noted that heart transplant recipients with eGFR,37 ml/min per 1.73 m 2 had worse survival than SHK recipients (59).…”
Section: What Is the Evidence To Support Left Ventricular Devices Fromentioning
confidence: 99%
“…Выделяют одномоментную, или симультанную (simultaneous), трансплантацию сердца-почки от одного и того же донора, а также последовательные (staged) транс-плантации сердца и почки от двух генетически раз-личных доноров [1]. В соответствии с протоколом «UNOS-Standard Transplant Analysis and Research» симультанной, или одномоментной, следует счи-тать трансплантацию сердца и почки, выполненную одна за другой в интервале не более 24 ч [2].…”
unclassified